Experimental modelling of local structure responses for high-speed planing craft in waves. (15th November 2020) - Begovic, Ermina; Bertorello, Carlo; Bove, Andrea; Garme, Karl; Lei, Xiangyu; Persson, Jonas; Petrone, Giuseppe; Razola, Mikael; Rosén, Anders
Abstract: The modelling of planing craft dynamics in waves and related fluid-structure interaction is a hard challenge due to the highly nonlinear, transient and stochastic nature of the whole process. This paper explores the prospectives of detailed experimental modelling of the local structure responses for high-speed planing craft in waves. A novel experimental setup is presented where a well-defined model structure is integrated into the hull bottom of a typical planing craft model. The model is instrumented for measuring strains in the model structure, related slamming pressures, craft rigid body motions and accelerations. The experimental setup is thoroughly described and motivated and crucial aspects of the setup are verified through testing in idealized static loading conditions and by modal analysis. The capabilities of the experimental setup are demonstrated through systematic experiments in regular waves. The most indicative results are presented and discussed in relation to corresponding results from time-domain simulations. The presented experimental modelling approach is concluded to enable uniquely detailed studies of the complete slamming related fluid-structure interaction process and provides a good tool for further research and development towards establishment of first principles-based methods for hydrodynamic and structure design of high-speed planing craft. Highlights: A unique setup for experimental modelling of the local structure responses for high-speed planing craft in waves is investigated. A model structure is developed, instrumented and verified through testing in idealized static loading conditions and by modal analysis and mounted in a planing hull model. Vertical motions, accelerations, impact pressures and structure response are measured in series of model tests in regular waves. Results are presented and compared against time-domain simulations performed with a numerical modelling approach. Both the experimental and numerical approaches are concluded to provide valuable tools for further research towards establishment of first principles-based methods.